2022
DOI: 10.21037/tcr-21-2776
|View full text |Cite
|
Sign up to set email alerts
|

Gastroparesis as a significant gastrointestinal adverse event during intensive chemotherapy for solid caner: a case report

Abstract: Background Proper management of chemotherapy-related gastrointestinal toxicities is essential to maximize therapeutic outcome for malignancies. Gastroparesis is an onerous syndrome characterized by delayed gastric emptying without gastrointestinal obstruction, but this has not been recognized as chemotherapy-related complication in solid malignancies. Here, we describe a case of gastroparesis possibly caused by neurotoxicity of taxane and platinum-based high-intensity chemotherapy against solid ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…The persistent contraction of the LES can be a consequence of radiation-induced injury to the vagus nerves 80 and/or chemotherapeutic drug-induced injury to the neurons of the myenteric plexus, which controls the motility of the digestive tract. 81,82 Vitton et al reported that 12 (60%) out of 20 patients with symptoms of dysphagia and history of cancers receiving radiotherapy or chemoradiotherapy to the cervical or thoracic esophagus had an abnormal pattern on EHRIM in which 1 (5%) patient was confirmed to have type II achalasia. 83 However, one of the pitfalls of their study was the lack of a control group to demonstrate the esophageal motility status in the non-irradiated subjects with matching age and sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The persistent contraction of the LES can be a consequence of radiation-induced injury to the vagus nerves 80 and/or chemotherapeutic drug-induced injury to the neurons of the myenteric plexus, which controls the motility of the digestive tract. 81,82 Vitton et al reported that 12 (60%) out of 20 patients with symptoms of dysphagia and history of cancers receiving radiotherapy or chemoradiotherapy to the cervical or thoracic esophagus had an abnormal pattern on EHRIM in which 1 (5%) patient was confirmed to have type II achalasia. 83 However, one of the pitfalls of their study was the lack of a control group to demonstrate the esophageal motility status in the non-irradiated subjects with matching age and sex.…”
Section: Discussionmentioning
confidence: 99%
“…The neurons of the ENS that control motility and peristalsis are located in the myenteric plexus, which lies between the circular and longitudinal layers of smooth muscles. The persistent contraction of the LES can be a consequence of radiation‐induced injury to the vagus nerves 80 and/or chemotherapeutic drug‐induced injury to the neurons of the myenteric plexus, which controls the motility of the digestive tract 81,82 . Vitton et al reported that 12 (60%) out of 20 patients with symptoms of dysphagia and history of cancers receiving radiotherapy or chemoradiotherapy to the cervical or thoracic esophagus had an abnormal pattern on EHRIM in which 1 (5%) patient was confirmed to have type II achalasia 83 .…”
Section: Discussionmentioning
confidence: 99%